Using banana waste biochar for simultaneous removal of heavy metals from raw real wastewater from the electroplating industry (2023)
The simultaneous removal of heavy metals (Fe2+, Zn2+, Ni+2, Cr2+, and Cu2+) using filters built with cheap and easily accessible materials was studied in raw real wastewater generated from an electroplating industry localized in Medellín-Colombia. Various synthesized materials from banana peel waste were used as adsorbents, including powdered dry biomass and functionalized (chemically treated with activating agents) and unfunctionalized biochars, all obtained via hydrothermal and pyrolytic synthesis. For comparison, a commercial activated carbon (CAC) was employed. Significant variations in both structural and surface characteristics were observed among the materials depending on the activating agents utilized. As it was raw wastewater, the coexistence of multiple metals posed challenges in the objective comparison of adsorbents. Thus, the normalization of the maximum adsorption capacity about various parameters (for example, the amount of adsorbent, the specific surface area, the type and abundance of superficial functional groups, or the diameter and volume of the pore) confirmed the complexity of this type of process. In general terms, CAC and unfunctionalized biochar exhibited the highest adsorption capacities (for most metals). This suggests that, when employing banana waste adsorbents for the simultaneous removal of heavy metals in electroplating industry wastewater, the functionalization processes (which involve energy consumption, reagent usage, and waste generation) may not be necessary.